International Speakers and Key- note Presentations (Mazandaran University of Medical Sciences, 2015)
Invasive fungal Infection is a major cause of mortality in patients with hematologic malignancy and hematopoietic stem cell transplant (HSCT). Invasive bronchopulmonary aspergillosis and invasive fungal sinusitis (IFS) are two important clinical presentations of Aspergillus in immunocompromised hosts. A descriptive cross-sectional study was performed on patients admitted to Taleghani hospital affiliated to Shahid Beheshti University of Medical Sciences, Tehran, Iran during October 2012-October 2013. Clinical data of 24 patients with IFS were reviewed. All patients had hematologic malignancies, and received broad spectrum chemotherapy. Moreover, demographics data, clinical characteristics, manifested symptoms and signs, underlying diseases and outcomes of the patients were assessed.